2021
DOI: 10.1002/adsc.202101169
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Isoquinolylselenocyanates and Quinolylselenocyanates via Electrophilic Selenocyanogen Cyclization Induced by Pseudohalogen (SeCN)2 Generated in situ

Abstract: A strategy for the synthesis of isoquinolylselenocyanates and quinolylselenocyanates through electrophilic selenocyanogen cyclization has been developed. The feature of this reaction is that the sequential process was induced directly by generated in situ pseudohalogen (SeCN) 2 generated in situ. Additionally, the obtained selenocyanates allowed functional group diversification, which could be potential intermediates for valuable compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…To probe the possible mechanism, the control experiments were conducted, , as shown in Scheme . The pseudohalogen (SeCN) 2 was generated from AgSeCN and NCS (Scheme a) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To probe the possible mechanism, the control experiments were conducted, , as shown in Scheme . The pseudohalogen (SeCN) 2 was generated from AgSeCN and NCS (Scheme a) .…”
Section: Resultsmentioning
confidence: 99%
“…The electrophilic cyclization of alkynes has been a powerful method for the construction of functionalized carbocycles and heterocycles, including the spirocyclic scaffolds . Very recently, we have successfully built the isoquinolylselenocyanates through electrophilic selenocyanogen cyclization, which combined the isoquinoline and selenocyanates (Scheme a) . Encouraged by the success of these experiments, we envisioned that the electrophilic selenocyanogen cyclization of biaryl ynones could provide a straightforward route to spiro[5.5]­trienones-fused selenocyanates (Scheme b).…”
Section: Introductionmentioning
confidence: 99%
“…Our literature survey showed that the existing approaches include a metal-free synthesis of thiocyanato-containing azaspirotrienediones via photocatalytic carbothiocyanation of N -phenylpropynamides ( Chen et al, 2019 ), a visible light-promoted carbon nitride-catalyzed thiocyanation of methylthiolated alkynones with NH 4 SCN affording the corresponding thiocyanated thioflavone products ( Zeng et al, 2021 ), and a TCCA/NH 4 SCN-mediated cyclization/thiocyanation of alkynyl aryl ketones enabling the synthsis of 3-thiocyanated chromones ( Xiao et al, 2021 ). Most recently, Zhou and co-workers reported the synthesis of isoquinolylsenocyanates and quinolylsenlenocyanates via electrophilic selenocyanogen cyclization induced by pseudohalogen (SeCN) 2 generated in situ ( Wang et al, 2022 ). Each of the above methods has its merits in preparing the corresponding S/SeCN-containing heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Very recently, we have developed a new method to construct selenocyanates through electrophilic selenocyanogen cyclization (Scheme 1c). [20] Inspired by these achievements and continuing our interest in the electrophilic cyclization, we designed that the substrates of alkynes can undergo the electrophilic selenocyanogen cyclization (Scheme 1d). Herein, we report a concise method to synthesize heterocyclicselenocyanates by electrophilic selenocyanogen cyclization.…”
mentioning
confidence: 99%
“…First, the pseudohalogen (SeCN) 2 is generated in situ from AgSeCN and NCS. [20] Under the activation of Lewis acid Et 2 O • BF 3 , the selenocyanate cation is generated, which could combine with substrate 1 to form the reactive species selenonium ion A. Then, the intermediate A undergoes an intramolecular cyclization and the leaving group Y (Me, H) is removed with the selenocyanate anion to give the heterocyclicselenocyanates product 2.…”
mentioning
confidence: 99%